Between existential mobility and intimacy 5.0: translocal care in pandemic times. (May 2023) - Cabalquinto, Earvin Charles B; Büscher, Monika
The COVID-19 pandemic has reconfigured every social, political, economic and cultural aspect of modern society. Millions of people have been stuck in lockdown within and across borders, national and regional terrains, in their homes and worse places. At this time of unprecedented change and 'stuckedness', digital communication technologies have served as a lifeline to forge and nurture communication, intimate ties and a sense of continuity and belongingness. But being stuck and simultaneously virtually mobile has brought many difficulties, tensions and paradoxes. In this paper we discuss first insights from a study with 15 members of the older Culturally and Linguistically Diverse (CALD) population in Victoria, Australia to explore experiences of being physically stuck and virtually mobile. We find practices of translocal care – ways of caring for distant others through digital technologies, has been made more complex by the pandemic and shaped by two dynamics: networked collective 'existential mobility', and a quantification of feeling that we call 'intimacy 5.0'.